Gentamicin-Loaded TiO2 Nanotubes as Improved Antimicrobial Surfaces for Orthopedic Implants - Draghi, Lorenza; Preda, Valeria; Moscatelli, Monica; Santin, Matteo; Chiesa, Roberto (Frontiers in Materials, 2020)
Titanium oxide nanotube arrays are extremely promising materials for localized drug delivery in orthopedic implants due to their excellent properties and facile preparation. TiO2 nanotubes can act as an effective drug reservoir to prevent bacterial colonization and implant infection and, at the same time, could promote tissue regeneration and effective osseointegration. Here, highly ordered TiO2 nanotubes (NTs) were synthesized by electrochemical anodization of titanium foils and the process parameters were varied in order to obtain a large range of NT diameters to evaluate its influence. The effect of NTs’ diameter on gentamicin loading/release and on osteosarcoma cell and bacterial adhesion was assessed. Anodization was confirmed as an easy and effective method to prepare highly ordered, open top nanotubes with predictable diameter as a function of imposed voltage. A lower amount of bacteria Staphylococcus Aureus adhesion was found on unloaded NTs surfaces at 24 h. When gentamicin was loaded, protracted release and antibacterial action was observed and bacteria adhesion was prevented on all NTs dimension. However, higher cell proliferation and a more favorable cell morphology was observed on smaller nanotubes, to support the indication toward a reduction in NTs diameter for the preparation of effective implant surfaces.